The Study of Tourism Comfort Climate Index in Desert Area (Case Study: Yazd Province) - Esmail Heydari Alamdarloo; Hassan Khosravi; Sahar Nasabpour Molaei (تحقیقات کاربردی علوم جغرافیایی)
Proper climate and adequate knowledge tourism and can be as an attractive or unpleasant factor for tourists. The purpose of this research is to evaluate the tourism climate of Yazd province as one of the most important provinces in the arid regions of the country. For determining the tourism presence comfort in the Yazd province, Tourism Climate Index (TCI) was used. In order to investigate tourism climate index data from 17 meteorological stations was used. Then by calculation sub-indexes and TCI, zoning of TCI and sub-indexes for Yazd province was done with ArcGIS environment. The results showed that October, May, November and April are the best months for tourism activities in Yazd province, and January, July, February and December have the lowest average of TCI index respectively. The most changes in TCI occurs in July and the lowest changes is in October. According to Scott & McBoyle classification, the TCI annual classification shows that Yazd province is placed in two classes: Bi-modal shoulder peak and Dry season peak. Generally, the mountainous area with an altitude of more than 2,700 to 3,000 meters and their surrounding areas when rainfall and lower temperatures is not a limiting factor have the best tourism conditions in the dry season. Other areas with less height of 2700 to 3000 meters have the best climatic conditions for tourism in the spring and autumn.